AGENT-BASED MODEL OF INTELLIGENT INFORMATION CONTROL SYSTEMS IN ECONOMICS - G. Chornous (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper deals with the problem of developing the effective information control system' model for economic subjects corresponding to the main trends of modern economic development (globalization, informatization, intellectualization, etc.). The basis of the system model development is proactive decision-making process as one that best matched to the current pace of information society development. Analysis of existing software and technology base for support of control processes in the economy demonstrates the need of the formation and implementation in practice hybrid intelligent information control systems, based on the integration of information analytics technology and other advanced IT. The agent multilevel model of intelligent information systems for proactive management of socio-economic system was recognized advantageous as one that provides distribution of solution generation between specialized agents, knowledge management, transitions between the processes of proactive management and the integration of different information systems, methods, modes of preparation and analysis within the same model. The structure of the model was proposed, it includes the groups of agents: data collection, monitoring, solutions generation, modelling, action, user preferences study and presentations. The analysis of the results of the model implementation in management practices demonstrates significant economic effect.